AN AUDITORY-BASED SPEAKER IDENTIFICATION SYSTEM IN ACOUSTIC NOISES - D. N. Kruchok; A. A. Petrovsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The speaker recognition system in acoustic noises with the use of anthropomorphic speech signal processing is considered. A transform based on the cochlear model and its applications for speaker recognition are described in details. The characteristic vector obtained on the basis of this transform used as features for speaker identification. Neural network of direct distribution as decision rules are used. The results of the developed recognition systems of speaker identification are given.